Natural Language Processing with Java : Techniques for Building Machine Learning and Neural Network Models for NLP, 2nd Edition. - M. Reese, Richard (Packt Publishing Ltd, 2018)
Natural Language Processing with Java will explore how to automatically organize text using approaches such as full-text search, proper name recognition, clustering, tagging, information extraction, and summarization. You will leverage the power of Java to extract relationships within different elements of text and documents.